Pengaruh Model Inquiry Based Learning (IBL) Menggunakan Media Wordwalll terhadap Kemampuan Membaca Pemahaman Murid Kelas V UPT SD Negeri 07 Mudiak Lawe - Zahara Putri Yuni; Dian Sarmita; Esa Yulimarta (Lentera: Jurnal Ilmiah Kependidikan, 2026)
This research is motivated by the low reading comprehension ability of students in class V of UPT SD Negeri 07 Mudiak Lawe, Sungai Pagu District, South Solok Regency. The purpose of this study is to determine the influence of the Inquiry Based Learning (IBL) learning model using Wordwall media on students' reading comprehension skills. This study uses a quantitative approach with a one-group pretest-posttest design research. The population and sample of this study are all students of class V UPT SD Negeri 07 Mudiak Lawe with a total of 20 students. The instrument used is in the form of an objective test that has been tested for validity. The results showed that students' reading comprehension ability after treatment was higher than before being treated. This is evidenced by the results of the hypothesis test analysis that the significance value  of the pretest and posttest of students is 40.61 ˃ 2.093. So it can be stated that H0 is rejected and H1 is accepted. Thus, it can be concluded that there is a significant influence in the application  of the Inquiry Based Learning (IBL) learning model using Wordwall media on the reading comprehension ability of students in grade V of UPT SD Negeri 07 Mudiak Lawe, Sungai Pagu District, South Solok Regency.